1994
DOI: 10.2337/diacare.17.10.1100
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Comparison of Metformin and Sulfonylurea, Alone and in Various Combinations: A double-blind controlled study

Abstract: Dose-effect titrated treatment with either metformin or glyburide promotes equal degrees of glycemic control. The former, but not the latter, is able to achieve this control without increasing body weight or hyperinsulinemia. Near-normal glycemia can be obtained by a combination of metformin and sulfonylurea, even in advanced NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
181
2
11

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(209 citation statements)
references
References 18 publications
15
181
2
11
Order By: Relevance
“…In contrast to other experimental studies [9,10,16], we observed no change in the course of weight after initiation of sulfonylurea treatment (Table 3). Weight loss is a common concomitant of the onset of metformin treatment [9,10,16], a finding which we cannot confirm either (Table 3). These results were possibly affected by the doctors' considerations about who would benefit from which drug treatment in our individualised treatment model.…”
Section: Weight Loss Due To Calorie Loss In Glucosuriacontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to other experimental studies [9,10,16], we observed no change in the course of weight after initiation of sulfonylurea treatment (Table 3). Weight loss is a common concomitant of the onset of metformin treatment [9,10,16], a finding which we cannot confirm either (Table 3). These results were possibly affected by the doctors' considerations about who would benefit from which drug treatment in our individualised treatment model.…”
Section: Weight Loss Due To Calorie Loss In Glucosuriacontrasting
confidence: 99%
“…It is commonly observed that treatment of type 2 diabetic patients with sulfonylureas [8][9][10] or insulin [10][11][12] is associated with weight gain. This effect of sulfonylureas and insulin could possibly aggravate the insulin-resistance syndrome associated with type 2 diabetes [2,13,14] and thereby counteract the otherwise beneficial effects of these agents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It also has beneficial effects in cardiovascular disease, impaired glucose tolerance and polycystic ovary syndrome through an insulinsensitizing effect [1] . However, metformin therapy is characterized by considerable inter-individual variability in clinical efficacy [2] . Some studies have shown that metformin is not metabolized but is transported by at least two organic cation transporters (OCTs), OCT1 and OCT2 [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…In type 2 diabetic patients with baseline HbA 1c (A1C) 8.5-9.0%, monotherapy with metformin (4,5) or sulfonylureas (6,7) reduces the A1C by ϳ1.5-2%. Addition of metformin to a sulfonylurea or vice versa provides a completely additive effect and decreases the A1C to Ͻ7.0% in ϳ60 -70% of patients (4,8,9). Mechanistically, optimal treatment in the remaining 30 -40% of individuals who do not achieve adequate glycemic control on metformin/sulfonylurea therapy remains unclear (8,10).…”
mentioning
confidence: 99%